Accelerated learning method using edmodo to increase students' mathematical connection and self-regulated learning - Yaniawati, R. Poppy; Kartasasmita, Bana G.; Kariadinata, Rahayu; Sari, Evi (Proceedings of the 2017 International Conference on Education and Multimedia Technology - ICEMT '17, 2017)
This study aims to analyze implementation of accelerated elearning method using edmodo media to increase mathematical connection ability and self-regulated learning of students. The research method employed was mixed method research with embedded design. Subjects of the study were eleventh grade students of a vocational secondary school in Tasikmalaya, Indonesia. Research instruments used were test for mathematical connection ability, questionnaire of students’ self-regulated learning, observation and interview guidelines. Statistical analysis were t-test, mann-whitney test, and two-way anova. results of this study showed that (1) mathematical connection abillity of high and low clasification students who studied used accelerated learning with edmodo was better than that of students who studied with conventional learning; (2) no differences were found in selfregulated learning of high and low classification students who studied used accelerated learning with edmodo was better than that of students who studied with conventional learning; (3) a positive correlation was found between mathematical connection ability and self-regulated learning students.
KerkoCite.ItemAlsoKnownAs: 10.1145/3124116.3124128 2129771:XDURBWJH 2486141:H5R6ZU56 5168324:Q2FXX6JR
Keywords: _AcademicRecoveryOECS